Intensywność treści w paratekstach prozy Pavla Rankova - Sojda, Sylwia (Przekłady Literatur Słowiańskich, 2017)
The Intensity in Paratexts of Pavol Rankov’s Prose The article concerns the issue of intensification in Polish and Slovakreviews of Pavo l Rankov’s prose. The review, as a form accompanying the main text, is treated as paratext. The linguistic category of intensification can be expressed in the text by the variety of linguistic means: derivational, morphological, lexical, and stylistic. These structures, with the collateral “intensifiers”, were cited and analysed in this study. The main role of intensification is to attract the language users’ attention to the part of a phrase. It can be obtained by a variety of linguistic means. There should be a distinction between exponents of intensity (in context) and the function of intensifiers (in narrow view). That is why there is an important methodological new proposal to isolate intensifiers as the other part of speech in the contemporary Polish. Intensifier is a modifier, which converts the meaning of another lexical unit by giving it more power, force, in contrast to the (wider) exponent of intensity, which can be a derivational, morphological, lexical, phraseological or syntactic and stylistic phenomenon. In the Slovak linguistics, the intensification of properties (for adjectives) is next to deminutiveness, one of the clearest and most diversified, according to expressiveness, onomasiological categories. Keywords: intensity, review, intensifiers, adverbs, modifiers, gradation, Slovak language